Archives, Open Government and National Security Balancing Concepts of Public Ownership with Security and Intelligence in Canada. Issue 3 (1st September 2020) - German, Daniel
ABSTRACT: Starting in 1967, with the issuance of an Order-in-Council by Canada’s Privy Council, the concept of providing Canadians access to their Federal Government Records was promulgated through their National Archives (now Library and Archives Canada - LAC). In the intervening decades, LAC has reviewed millions of pages of Security and Intelligence Records and, whenever possible, released them. Now, as the Canadian Federal Government examines changes to the Access to Information Act, as well as changes to Canada’s National Security systems, there is a new commitment to National Security Transparency. The intent of this paper is to examine the historic provision of archival access to the records of Canada’s Federal Security and Intelligence Records, in particular to the archival records of the Canadian Security Intelligence Service (CSIS). Through a proper application of the terms of the Access to Information Act to the Canada’s Federal Security and Intelligence files, carried out in consultation with Canada’s intelligence community, Library and Archives Canada has embraced its responsibilities to Governmental Openness and the needs and requirements of National Security. In doing so, LAC has worked to balance legislatively mandated commitment to chart a course between desirable accessibility and the operational needs of Canada’s Security/Intelligence community.